What 31 provinces reveal about growth in China - Eeva Kerola; Benoît Mojon (Bank of Finland, Bank of Finland Institute for Emerging Economies (BOFIT), 2021)
It is important to understand the growth process under way in China. However, analyses of Chinese growth became increasingly more difficult after the real GDP doubling target was announced in 2012 and the official real GDP statistics lost their fluctuations. With a dataset covering 31 Chinese provinces from two decades, we have substantially more variation to work with. We find robust evidence that the richness of the provincial data provides information relevant to understand and project Chinese aggregates. Using this provincial data, we build an alternative indicator for Chinese growth that is able to reveal fluctuations not present in the official statistical series. Additionally, we concentrate on the determinants of Chinese growth and show how the drivers have gone through a substantial change over time both across economic variables and provinces. We introduce a method to understand the changing nature of Chinese growth that can be updated regularly using principal components derived from the provincial data.
URN:NBN:fi:bof-202101281076
Keywords: C38; E01; E3; P2; 330; China; GDP; provincial data; business cycles; principal component